2023
DOI: 10.1111/1751-7915.14312
|View full text |Cite
|
Sign up to set email alerts
|

Exploring engineered vesiculation by Pseudomonas putida KT2440 for natural product biosynthesis

Nora Lisa Bitzenhofer,
Carolin Höfel,
Stephan Thies
et al.

Abstract: Pseudomonas species have become promising cell factories for the production of natural products due to their inherent robustness. Although these bacteria have naturally evolved strategies to cope with different kinds of stress, many biotechnological applications benefit from engineering of optimised chassis strains with specially adapted tolerance traits. Here, we explored the formation of outer membrane vesicles (OMV) of Pseudomonas putida KT2440. We found OMV production to correlate with the recombinant prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 101 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…[31][32][33] It has recently been shown that OMV release by hosts like E. coli and P. putida can be genetically engineered thereby supporting the recombinant production of hydrophobic natural compounds. [34,35] One approach to such engineering is the downregulation or deletion of genes with an essential function in the formation of the cell envelope. [36][37][38] Thus, two strains with knocked-out genes mlaE and pvdQ, respectively, previously identified as suitable targets for engineering of vesiculation (see Figure S6), [35] were tested for arcyriaflavin A production (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33] It has recently been shown that OMV release by hosts like E. coli and P. putida can be genetically engineered thereby supporting the recombinant production of hydrophobic natural compounds. [34,35] One approach to such engineering is the downregulation or deletion of genes with an essential function in the formation of the cell envelope. [36][37][38] Thus, two strains with knocked-out genes mlaE and pvdQ, respectively, previously identified as suitable targets for engineering of vesiculation (see Figure S6), [35] were tested for arcyriaflavin A production (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] One approach to such engineering is the downregulation or deletion of genes with an essential function in the formation of the cell envelope. [36][37][38] Thus, two strains with knocked-out genes mlaE and pvdQ, respectively, previously identified as suitable targets for engineering of vesiculation (see Figure S6), [35] were tested for arcyriaflavin A production (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aromatics, acids and. alcohols) based on a variety of carbon substrates (Bitzenhofer et al, 2023;Dvořák & de Lorenzo, 2018;Loeschcke & Thies, 2020;Tiso et al, 2022;. However, P. putida relies solely on oxygen as the terminal electron acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…The microorganisms that can synthesize phenazine compounds mainly include Pseudomonas [6], Streptomyces [7], and Methanosarcina [8]. The fermentation time of Streptomyces is much longer than that of Pseudomonas; thus, its fermentation cycle is longer, which is not conducive to industrial production.…”
Section: Introductionmentioning
confidence: 99%